An adaptive arresting vessel device for protecting bridges over non-navigable water against vessel collision. (15th June 2021) - Chen, W.; Wang, Y.G.; W.Li,; Yang, L.M.; Liu, J.; Dong, X.L.; Zhu, H.H.; Wang, F.
Highlights: An adaptive arresting vessel device (AAVD) was developed to protect bridges over non-navigable water. An energy absorbing structure was designed to consume enormous kinetic energy of vessel. The feasibility and reliability of AAVD was validated by experiments and simulations. The engineering structures of AAVD were constructed successfully for Pingtan Bay Bridge. Abstract: There is a large number of bridges over non-navigable water, and the safety protection against vessel collision is worthy of attention. In this paper, a new adaptive arresting vessel device (AAVD) was developed to protect bridges over non-navigable water against vessel collisions. The AAVD mainly consists of moored boats, mooring chains and anchors, adaptive buoys, arresting nets, trigger devices and energy absorbing devices with constant resistant force. The motion behavior of the adaptive buoys was analyzed theoretically using rigid-body kinematics. Enormous kinetic energy of the vessel is consumed by the deformation and fracture of a series of cables. Through the scale model experiments, the key parameters of the AAVD on the arresting effectiveness are discussed and determined, and the feasibility of AAVD has been preliminarily verified. The full-scale test section of the AAVD has been constructed, and the arresting vessel collision tests have been carried out. The experimental results show that the AAVD can effectively stop a yaw ship, and verify the feasibility and reliability of the technical principle and engineering design. Hence, the AAVD can achieve the purpose of protecting the safety of bridges over non-navigable water. Numerical simulation of the AAVD has been performed by using hydrodynamic analysis ANSYS-AQWA software. Numerical results are in reasonable agreement with the experimental and theoretical simulation results.